1999
DOI: 10.1017/s0033291799008399
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of the risk of recovery from DSM-III-R social phobia

Abstract: Our data indicate that social phobia in the general population is a chronic and unremittent disorder. Determinants of recovery are rooted in distal childhood circumstances, disorder attributes, and the physical and mental health status of individuals over the life course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 46 publications
4
48
0
1
Order By: Relevance
“…This raises the question why so many prior studies failed to detect the genuinely high proportion of the population with the disorder. Lower estimates in some studies than others , Andrews et al, 2001, Bijl et al, 1998, Davidson et al, 1994, DeWit et al, 1999, Grant et al, 2005, Stein et al, 1996, Stein et al, 1994 may have resulted from differences in methodology or assessment (e.g., variation in the number and kinds of social situations assessed or in the diagnostic system used) or may reflect genuine differences between countries or cultures in the prevalence of the disorder . Clinical validation studies of the sort included in the NCS-R would be needed to adjudicate between these possibilities.…”
Section: Discussionmentioning
confidence: 95%
“…This raises the question why so many prior studies failed to detect the genuinely high proportion of the population with the disorder. Lower estimates in some studies than others , Andrews et al, 2001, Bijl et al, 1998, Davidson et al, 1994, DeWit et al, 1999, Grant et al, 2005, Stein et al, 1996, Stein et al, 1994 may have resulted from differences in methodology or assessment (e.g., variation in the number and kinds of social situations assessed or in the diagnostic system used) or may reflect genuine differences between countries or cultures in the prevalence of the disorder . Clinical validation studies of the sort included in the NCS-R would be needed to adjudicate between these possibilities.…”
Section: Discussionmentioning
confidence: 95%
“…[2,3] In the absence of treatment, SP is a chronic lifelong disorder with little spontaneous remission course. [4] The DSM-IV-TR [5] distinguishes between generalized social phobia (GSP) and non-generalized or specific social phobia (SSP) subtypes. GSP is characterized by fear of multiple social situations, whereas SSPs fears are circumscribed to a small number of situations.…”
Section: Introductionmentioning
confidence: 99%
“…It is a common disorder: epidemiological studies (Fresco, Erwin, Heimberg, & Turk, 2000;Kessler et al, 1994;Kringlen, Torgersen, & Cramer, 2001) have found lifetime prevalence rates of about 13%. Left untreated, the disorder has a chronic course (DeWit, Ogborne, Offord, & MacDonald, 1999;Keller, 2003), and severely impairs social role functioning and career progression (Wittchen & Fehm, 2003). It also represents an influential risk factor for suicidal behavior (Keller, 2003).…”
Section: Introductionmentioning
confidence: 99%